Posterior white matter disease distribution as a predictor of amyloid angiopathy - Thanprasertsuk, Sekh (Lippincott Williams & Wilkins, 2014)
OBJECTIVES: We sought to examine whether a posterior distribution of white matter hyperintensities (WMH) is an independent predictor of pathologically confirmed cerebral amyloid angiopathy (CAA) and whether it is associated with MRI markers of CAA, in patients without lobar intracerebral hemorrhage. METHODS: We developed a quantitative method to measure anteroposterior (AP) distribution of WMH. A retrospective cohort of patients without intracerebral hemorrhage and with pathologic evaluation of CAA was examined to determine whether posterior WMH distribution was an independent predictor of CAA (n = 59). The relationship of AP distributions of WMH to strictly lobar microbleeds (MBs) (n = 259) and location of dilated perivascular spaces (DPVS) (n = 85) was examined in a separate cohort of patients evaluated in a memory clinic. RESULTS: A more posterior WMH distribution was found to be an independent predictor of pathologic evidence of CAA (p = 0.001, odds ratio [95% confidence interval] = 1.19 [1.07–1.32]), even in the subgroup without lobar MBs (p = 0.016, odds ratio [95% confidence interval] = 1.18 [1.03–1.36]). In the memory clinic cohort, strictly lobar MBs were independently associated with more posterior WMH distribution (p = 0.009). AP distribution of WMH was also associated with location of DPVS (p = 0.001), in that patients with predominant DPVS in the white matter over the basal ganglia harbored a more posterior WMH distribution. CONCLUSIONS: Our results suggest that AP distribution of WMH may represent an additional marker of CAA, irrespective of the presence of lobar hemorrhages. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that there is a significant association between the AP distribution of WMH on MRI with the presence of pathologically confirmed CAA pathology.